Mammal species composition reveals new insights into Earth's remaining wilderness. Issue 7 (6th April 2020) - Belote, R Travis; Faurby, Søren; Brennan, Angela; Carter, Neil H; Dietz, Matthew S; Hahn, Beth; McShea, William J; Gage, Josh
Abstract : Maps of the human footprint allow ecologists to identify the wildest lands on the planet, track their decline, and prioritize wildland conservation efforts. Other research efforts have mapped biological intactness and identified conservation priorities to protect biodiversity. However, little research has involved the use of historical references to evaluate intactness of species composition globally. We used a dataset estimating historical and current distributions of mammals to address whether the wildest places on Earth support the most intact mammal communities. Contrary to our expectations, we found that the global human footprint was not strongly correlated with mammal community intactness and uncovered surprising situations where both the human footprint and mammal species intactness were high, and other examples where both were low. Our results could be used to enhance maps and estimates of global wilderness areas by identifying wild and intact regions, while also prioritizing conservation of intact but human‐modified landscapes.